Pengaruh Pembinaan Disiplin dan Motivasi Kerja Terhadap Kinerja Guru di SMK XYZ - Roby, Furqon Abdul; Prabowo, Juddy (Syntax Corporation, 2025)
One of the main components of educational success in schools is teacher performance. However, at XYZ Vocational High School, many teachers still have low performance. This research design is based on a quantitative approach with a research population of 46 permanent teachers. This study focuses on testing the interaction of discipline coaching and work motivation variables in determining teacher performance with assessments carried out partially and simultaneous. Instruments in the form of observation, interviews, and questionnaires were used to collect research data, while testing was carried out through a multiple linear regression analysis model along with a coefficient of determination processed using SPSS software version 27. From the processing results, it is known that discipline coaching plays a positive role in improving performance and performance achievement increases along with the presence of directional work motivation, and the results of simultaneous analysis show that the contribution of discipline coaching and teacher performance is significantly influenced by the presence of work motivation which is tested simultaneously.